2022
DOI: 10.3126/nepjoph.v14i1.31199
|View full text |Cite
|
Sign up to set email alerts
|

Development of Immersive Virtual Reality Environment for Assessment of Functional Vision in people with Low Vision: A Pilot Study

Abstract: Introduction: Virtual Reality technology helps in creating virtual environments for evaluation of visual performance of low vision individuals with holistic experience. The purpose of this study was to develop a virtual reality (VR) platform for the objective assessment of functional vision in patients with low vision in two categories, central and peripheral vision loss . Materials and methods: Focus group discussions (FGD) were organized to understand the difficulties faced on a day to day basis by patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…There are only a few studies illustrating the promising use of such technologies, such as prototype tools for identifying vision-related disabilities in patients with glaucoma (e.g., [18,19]). Prototype applications for functional vision assessment have also been investigated; however, these tools focus on patients with low vision and were only tested in lab settings (e.g., [20,21]).…”
Section: Of 21mentioning
confidence: 99%
See 1 more Smart Citation
“…There are only a few studies illustrating the promising use of such technologies, such as prototype tools for identifying vision-related disabilities in patients with glaucoma (e.g., [18,19]). Prototype applications for functional vision assessment have also been investigated; however, these tools focus on patients with low vision and were only tested in lab settings (e.g., [20,21]).…”
Section: Of 21mentioning
confidence: 99%
“…VR is also a technology that allows supporting vision training [8], which can help train, e.g., stroke patients [22] or the vision of children with OMD [23]. Since many FVPs, and in particular OMDs, can be helped by training [24], to see the effects of the training, this should also incorporate screening possibilities [20,21]. According to our current knowledge, there is no VR application for screening OMD and no VR eye-training application incorporating the possibilities of screening, except an experimental study implementing a laptop-based application to screen FVPs and developing an immersive virtual reality (VR)-based prototype and evaluating its usability [25], motivating this research.…”
Section: Of 21mentioning
confidence: 99%
“…Recently there has been increasing interest in using VR in research based around visual impairments. Some examples include walking canes that work in VR to allow visually impaired people to navigate a virtual world [15], analysing the wayfinding ability of those with glaucoma compared to those with normal vision in VR [16], assessing if VR is a viable assistive technology for the visual impaired (it was found that it can be) [17], and also attempting to develop an objective measure of a person's visual field using VR [18]. Research done related to AMD has investigated creating assistive technologies using VR to help those with AMD by magnifying parts of the user's view to compensate for their vision loss [19].…”
Section: Introductionmentioning
confidence: 99%